Industry Clustering Model on the Indonesia Stock Exchange in the COVID-19 Pandemic Era Using K-Means - Saumananda Suroso, Nurinda; Heikal, Jerry (Emerging Markets : Business and Management Studies Journal, 2022)
The COVID-19 pandemic has greatly affected the sustainability of large and small businesses around the world. The government of the capital city of DKI Jakarta implemented a special policy by announcing the implementation of Large-Scale Social Restrictions or PSBB starting April 2020 to tackle the spread of COVID-19. Given the situation in the year 2020, this study was conducted to determine whether Covid-19 has an impact on industries listed in Indonesia Stock Exchange (IDX) based on the 2020 financial report. This quantitative study uses the K-Means Clustering algorithm to group similar industries based on its Debt to Equity Ratio, Operating Profit Margin, and Sales Growth. Data is processed using Python with Anaconda and Jupyter Notebook as the IDE platform. From 50 industries that were sampled, 8 industries were very negatively affected, 3 industries were negatively affected, 28 industries were neutrally affected, 10 industries were positively affected, and 1 industry was very positively affected.